what's up? Simple power rule:
12x^2 + 6/3
y = 4 x^3 + 6/3 x
Enter the derivative: y'=???
3 answers
the equation is
4x^3 + 6/3x (4x cubed plus 6 over 3x)
4x^3 + 6/3x (4x cubed plus 6 over 3x)
ah- a few parentheses would help
(4x^3 + 6)/3x
just divide by 3x:
4/3 x^2 + 6/(3x) = 4/3 x^2 + 2/x
f' = 8/3 x - 2/x^2
Or, using the quotient rule,
[(12x^2)(3x) - (4x^3+6)(3)]/(3x)^2
= (36x^3 - 12x^3 - 18) / 9x^2
= (24x^3-18) / 9x^2
= (8x^3-6) / 3x^2
= 8/3 x - 2/x^2
(4x^3 + 6)/3x
just divide by 3x:
4/3 x^2 + 6/(3x) = 4/3 x^2 + 2/x
f' = 8/3 x - 2/x^2
Or, using the quotient rule,
[(12x^2)(3x) - (4x^3+6)(3)]/(3x)^2
= (36x^3 - 12x^3 - 18) / 9x^2
= (24x^3-18) / 9x^2
= (8x^3-6) / 3x^2
= 8/3 x - 2/x^2